2020
DOI: 10.1039/d0nr04105j
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous catalysis by ultra-small bimetallic nanoparticles surpassing homogeneous catalysis for carbon–carbon bond forming reactions

Abstract: Palladium catalyzed cross-coupling reactions represent a significant advancement in contemporary organic synthesis as these reactions are of strategic importance in the area of pharmaceutical drug discovery and development. Supported palladium-based...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…As such, a variety of carriers with different types and morphologies are explored to enhance the activity of the catalyst to modulate the growth of active NPs and the interaction between the NPs and carrier. The inorganic materials (activated carbon, metal oxide/hydroxide, silica, zeolite, and molecular sieves), organic materials (polymers and resins), and other organic–inorganic composites have been widely investigated to support the metal NPs. ,, As a member of carriers, the two-dimensional (2D) layered hydroxide has exhibited intriguing superiorities to support the metal NPs, e.g., high specific surface areas, tunable chemical properties, and accessible surface sites. , For example, Nakagaki and co-workers have first proposed to adsorb an iron porphyrin anion on the surface of a layered hydroxide crystal to obtain a composite material, which shows superior catalytic activity for the cyclooctane and cyclohexane oxidation. The high catalytic performance is ascribed to the easy access of the reactant to the catalytic sites. , EI-Shall and co-workers synthesized a series of Pd-based catalysts using functional layered reduced graphene oxide as the carrier, which has enhanced catalytic activity in microwave-assisted C–C cross-coupling reactions. Liu and co-workers used the layered hydroxide to load Pd NPs for the Heck reaction, which exhibits a high catalytic efficiency benefiting from the interaction between the Pd NPs and exfoliated hydroxide nanosheets with substantial basic sites. , Moreover, different researchers have found that the surface functional group in the layered hydroxide might function as a basic ligand for anchoring the Pd NPs and play a synergistic effect with the Pd NPs in the catalytic reaction to improve the catalytic activity. , Therefore, we consider it feasible that a catalytic impeller combined with Pd NPs anchored onto the layered hydroxide may provide a pathway to achieve the high catalytic activity, mass transport, and good recycling.…”
Section: Introductionmentioning
confidence: 99%
“…As such, a variety of carriers with different types and morphologies are explored to enhance the activity of the catalyst to modulate the growth of active NPs and the interaction between the NPs and carrier. The inorganic materials (activated carbon, metal oxide/hydroxide, silica, zeolite, and molecular sieves), organic materials (polymers and resins), and other organic–inorganic composites have been widely investigated to support the metal NPs. ,, As a member of carriers, the two-dimensional (2D) layered hydroxide has exhibited intriguing superiorities to support the metal NPs, e.g., high specific surface areas, tunable chemical properties, and accessible surface sites. , For example, Nakagaki and co-workers have first proposed to adsorb an iron porphyrin anion on the surface of a layered hydroxide crystal to obtain a composite material, which shows superior catalytic activity for the cyclooctane and cyclohexane oxidation. The high catalytic performance is ascribed to the easy access of the reactant to the catalytic sites. , EI-Shall and co-workers synthesized a series of Pd-based catalysts using functional layered reduced graphene oxide as the carrier, which has enhanced catalytic activity in microwave-assisted C–C cross-coupling reactions. Liu and co-workers used the layered hydroxide to load Pd NPs for the Heck reaction, which exhibits a high catalytic efficiency benefiting from the interaction between the Pd NPs and exfoliated hydroxide nanosheets with substantial basic sites. , Moreover, different researchers have found that the surface functional group in the layered hydroxide might function as a basic ligand for anchoring the Pd NPs and play a synergistic effect with the Pd NPs in the catalytic reaction to improve the catalytic activity. , Therefore, we consider it feasible that a catalytic impeller combined with Pd NPs anchored onto the layered hydroxide may provide a pathway to achieve the high catalytic activity, mass transport, and good recycling.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the preparation method is highly reproducible. Finally, even though the samples which were not subjected to high-temperature annealing, i.e., Pt­(M)/CB-R (M = Ø, Ni, Co), showed low activity and stability for the application in PEMFCs, the existence of a bottom-up approach of such simplicity for the synthesis of nanoparticles with sizes of about 1 nm is relevant for other catalysis applications …”
Section: Resultsmentioning
confidence: 99%
“…El-Shall et al found that ultra-small CuPd bimetallic nanoparticles deposited on a mesoporous-fumed silica support could be participated efficiently to the Suzuki-Miyaura coupling reaction of aryl bromides to give the corresponding coupling product within 30 min [159]. Bae, Byun, and Kim et al prepared small and large Au NPs stabilized in mesoporous TiO 2 and poly(N-isopropylacrylamide) particles, respectively.…”
Section: Porous Materialsmentioning
confidence: 99%